(untitled) (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: Gastrointestinal infection is a major cause of diarrhea, anemia, malnutrition and responsible for reducing physical and mental development especially in children. This study aimed to investigate the prevalence of the intestinal pathogens in the slum-dwelling population in Kaski, Nepal. Material and Methods: A cross-sectional study was conducted in August-September 2012 in slum-dwelling community. Overall 166 human faecal samples were collected and examined using formal ether sedimentation method. Results: The prevalence of gastrointestinal infections in slum-dwelling population was found to be 24.1%. The magnitude of infection was higher (26.9%) among females compared to males. The difference was not statistically significant (P > 0.05). The prevalence of infection was higher (37.0%, P > 0.05) in Dalit group. Children (≤10 years) had higher rate of infection than older people. 22% subjects had single and 2.4% had multiple infections. In the overall population, 12.7% had G. lamblia followed by 5.4% Ascaris lumbricoides, 4.8% Hymenolepsis nana and 3.6% Trichuris trichuria. Conclusion: Gastrointestinal infections were common in the slum-dwelling populations. Lack of health education and safe drinking water contributed higher infection rate in the community. Increased exposure time to the contaminated water and gender disparity had influenced the rate of infection. Due to the semi-urban area with absence of moist soil, protozoan infection was prevalent than helminth infections.